SmartCalc Guide: advancing mathematical fluency through digital calculator integration - Andu, Yusrina; Yaacob, Nurul Aityqah; Ahmad, Siti Noor Dina; Mohd Ruslan, Siti Zaharah; Jaafar, Zuraida (2025)
Scientific calculators have become a compulsory partner for students in studying mathematical concepts. These devices enable students to visualize, compute, and explore basic and multiple equations as well as formulas in a user-friendly manner. However, many students often find it challenging to utilize the full potential of these calculators. Hence, the SMARTCALC GUIDE is introduced to them to improve their mathematical fluency in using scientific calculators. The research was conducted among 125 students from different academic programs as well as mathematics courses at UiTM Kampus Kuala Pilah, assessing improvements in scientific calculator efficiency as well as competence by taking a pretest and post-test. Out of 125 participants, 80% students have agreed that SMARTCALC GUIDE improved their scientific calculator knowledge compared to before. Descriptive statistics revealed a major increase in the mean scores from the pre-test (M = 2.23, SD = 2.05) to the post-test (M = 6.52, SD = 2.38), indicating marked improvement. About 76.8% students agreed that this GUIDE has increase their confidence level in using scientific calculator. A majority (86.4%) of the participants agreed that using a scientific calculator significantly helped them solve mathematical problems more quickly. These findings show that SMARTCALC helped students not only understand the concepts of mathematics more efficiently but also boosted their confidence in applying these tools in other future courses. Thus, by enhancing students’ proficiency with scientific calculators, the SMARTCALC GUIDE has significantly improved their mathematical fluency, deepened their understanding, and strengthened their problem-solving abilities.